Metabolic engineering of Geobacillus thermoglucosidasius for utilisation of biomass and production of 3-hydroxypropoinic acid - Bashir, Zeenat (2018)
The continued extraction and exploitation of finite, fossil fuel reserves to meet the worlds’ energy and chemical demands is wreaking environmental havoc on the planet, most notably through climate change as a consequence of increased greenhouse gas (GHG) emissions. One solution to this problem is to use microorganisms that are able to convert renewable resources, such as lignocellulosic biomass, into the chemicals and fuels that society needs. This process requires that lignocellulosic biomass is hydrolysed by glycosyl hydrolases (GHs) into readily metabolizable molecules, such as hexose or pentose sugars, before being converted to ethanol or platform chemicals by fermentative organisms. Those fuels produced from biomass are termed second generation biofuels. Currently the cost of commercial enzymes used for the hydrolysis step remains a considerable economic barrier for production of second-generation biofuels or chemicals. This cost constraint could potentially be circumvented through consolidated bioprocessing (CBP), whereby the microorganism responsible for production of the chemical fuel is also able to bring about the deconstruction of biomass through the production of the requisite hydrolytic enzymes. The present study, therefore, focused on engineering a thermophilic, ethanol-producing, bacterium, Geobacillus thermoglucosidasius NCIMB 11955, which can utilise lignocellulosic biomass without the addition of expensive, exogenous hydrolytic enzymes. To achieve this, genes encoding CelA (Clostridium thermocellum), Cel6B (Thermoanaerobacter fuscii), CglT (Thermoanaerobacter brockii) and CelA (Caldicellulosiruptor bescii) were heterologously expressed in G. thermoglucosidasius. The engineered strains were shown to more effectively utilise pretreated wheat straw compared to the parental strain. Integration of cglT into the genome of ethanologenic G. thermoglucosidasius LS242 strain as well as expression on autonomous plasmid of either celAcb or celAct-cel6B resulted in the recombinant strains BZ243 and BZ244, respectively. These strains produced 4.2- and 3.7 mM ethanol, respectively from pretreated straw. The ability of the organism to produce 3-hydroxyproprionic acid (3-HP) from glucose through the malonyl-CoA pathway was also investigated. To accomplish this, a M. sedula gene encoding acetyl-CoA carboxylase (ACC) was expressed in G. thermoglucosidasius, together with genes encoding a bifunctional or monofunctional malonyl-CoA reductase (MCR) from either C. aurantiacus, M. sedula or S. tokodaii in combination with genes encoding a malonate-semialdehyde reductase (MSR) from either M. sedula or S. solfataricus. When these gene sets were placed under the transcriptional control of Pldh promoter, and the resultant organisms grown aerobically in shake-flasks with glucose as a sole carbon source, production of 3-HP ranged from 3.0-3.8 mM. In conclusion, engineered strains of G. thermoglucosidasius capable of either producing bioethanol or 3-HP could form the basis of a process for low-cost biomass processing and the production of chemicals or fuels.